Modeling Driver Behavior in a road network with route choice based on real time traffic information - Gao Feng (Institute of Advanced Engineering and Science, 2014)
Intelligent Transportation Systems (ITS) applications require a thorough understanding of drivers' route choice behavior in a complex network under real-time information. The purpose of this paper is to describe and model driver route choice behavior in a road network based on real time traffic information at the disaggregate individual level and from a psychological decision-making process perspective. The framework of routing choice and driver dynamic route choice behavior model that uses concepts from Decision Field Theory (DFT) and Bayesian belief network (BBN) is proposed. A real-time planning algorithm for route choice processes is discussed in great detail. Using this algorithm, a driver develops his route dynamically until he reaches his destination. The simulation results show that the combination of DFT and BBN can effectively describe the driver's travel dynamics behavior. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4466